Beyond parody critical analysis of Michael's V 15 popular song - Guanzon, Mary Hyazinth (2009.)
This study is written to analyze the 15 songs by Michael V. using Linda Hutcheon's concept of parody. It aims to examine the ?parodic? statements in Micael V?s songs and identify the different institutions being parodied in these songs. The analysis starts by reviewing relevant literatures through library and internet researches. The songs are randomly selected and are based on their availability. The songs reveal that indeed there are institutions (people, tradition and the likes) that are parodied. Not only did the songs reveal that but they also highlight some socially relevant issues. Other than that, the new songs serve as commentary to the old songs. Parody is used so as to give importance to the issues but at the same time mask it. As the thesis progresses, more of these parodies are discussed.
Thesis (Undergraduate, Bachelor of Arts in Literature. University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Michael V; Songs